EVALUATION OF DIARRHEA SURVEILLANCE SYSTEM IN MAGETAN REGENCY HEALTH OFFICE 2023 USING SURVEILLANCE ATTRIBUTES: Evaluasi Sistem Surveilans Diare di Dinas Kesehatan Kabupaten Magetan Tahun 2023 Berdasarkan Atribut Surveilans - Tajuddin AT, Nur Afdaliah; Isfandiari, Muhammad Atoillah; Yudi Purnomo, Agoes (Jurnal Berkala Epidemiologi, 2025)
Background: Diarrhea prevalence in 2023 in Magetan Regency was reported for all age groups at 59.40% and for children under five at 96.53%. The preliminary study found several problems in the recording and reporting system of Diarrhea in the Magetan Regency. Purpose: To describe the quality of the diarrhea surveillance system implemented in Magetan Regency Health Office based on surveillance system attributes assessment. Methods: Descriptive research with an evaluation study design. An evaluation was conducted on the diarrhea surveillance system in 2023 in the Magetan Regency Health Office. The respondents of this study were 23 people. Data was collected using questionnaires through Google Forms, interviews, and document studies. Data analysis was carried out and presented descriptively using tables and narratives. Results: Evaluation of the diarrhea surveillance system based on the assessment of surveillance attributes shows that the diarrhea surveillance system in Magetan Regency is simple, flexible, of high data quality, sensitive, highly acceptable, timely, and highly stable. However, the system is not representative, and the positive predictive value cannot be calculated. Conclusion: The implementation of the diarrhea surveillance system in Magetan Regency has been running well, mostly supported by the completeness of surveillance attributes. The evaluation results show that the system is simple, flexible, has high data quality and acceptability, is sensitive, timely, and highly stable. However, the system is not representative, and the PVT cannot be calculated.